Illicit temptations - Robert, Katee (Katee, Robert. Make me, 2024)
"What if the one person you shouldn't want is the one you can't resist? Make Me Yours. Becka Baudin gets what she wants, and she wants Aaron Livingston--but only for a quick affair. Weeks later, her coveted freedom starts to disappear thanks to a plus sign on a pregnancy test. Aaron insists she move in to his penthouse and commit to a relationship, but Becka demands he give her space without pushing for more. They are total opposites--with different jobs, interests, lives. But their chemistry keeps pushing them together...for better or for worse? Make Me Need. Trish Livingston desperately needs her new job. Which means putting up with the world's grumpiest boss--who is also her brother's best friend and business partner, Cameron O'Clery. The way he looks at her is pure disdain...but when he touches her, it's pure fire. With family and business ties at stake, they are not supposed to be together. There's a fine line between hate and lust, and they are going to cross it...but at what cost?"--